Effect of grand multiparity on adverse maternal outcomes: A prospective cohort study - Dasa, Tamirat Tesfaye; Okunlola, Michael A.; Dessie, Yadeta (Frontiers in Public Health, 2022)
Background: Grand multiparity remains a risk factor for a wide range of obstetric complications, especially in developing countries. It has been shown to increase the risks of medical and obstetric complications during pregnancy. However, in a research setting, the risk factors associated with adverse maternal outcomes have yet to be adequately investigated among grand multiparity. Objective: This study aimed to investigate the effect of grand multiparity on adverse maternal outcomes in selected public hospitals in the Sidama Region State of Ethiopia. Methods: A prospective cohort study design was employed on 837 pregnant women who were admitted from January 1 to August 31, 2021. The study subjects were recruited during admission for labour and delivery. Every woman who was admitted to labour wards was screened for eligibility. The exposed group in this cohort was grand multiparity, and the non-exposed group was multiparity. The risk factors for adverse maternal outcomes in grand multiparity were investigated using multivariable Poisson regression analysis. The risk factor was reported as an adjusted risk ratio (ARR) with a 95% confidence interval (CI). Statistical significance was declared when the P-value was less than 0.05. Results: The overall cumulative incidence of adverse maternal outcomes was 39.9% (95%CI: 36.6%, 43.4%) in the cohort. Among exposed groups, the incidence of adverse maternal outcomes was 47.1% (95%CI: 41.0–53.2) and 36.3% (95% CI: 32.3–40.6) in the multiparity. When compared to multiparous women, grand multiparity was associated with a greater risk of postpartum hemorrhage (ARR = 2.1; 95%CI: 1.6-2.7) and malpresentation (ARR = 1.3; 95% CI: 1.01-1.7). Conclusion: Pregnant women with grand multiparity have a higher incidence of adverse maternal outcomes. Grand multiparity was associated with an increased risk of adverse maternal outcomes such as postpartum bleeding and malpresentation. In low-resource settings, we recommend that community health education, the provision of accessible and effective contraceptive services, and increased awareness of the adverse maternal outcome among grand multiparity during pregnancy on obstetric performance should be prioritised. Also, the risk factor can be effectively decreased with good antenatal care and delivery by trained health providers.